2018
DOI: 10.1111/ijcp.13278
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to excessive polypharmacy (≥15 medications) in an outpatient population from Colombia

Abstract: Summary Aims To determine the frequency of excessive polypharmacy (≥15 medications) in an outpatient population from Colombia and the variables associated with this condition. Methods A cross‐sectional study using a systematised database of 6.2 million affiliates of the Colombian Health System. All patients treated uninterruptedly with 15 or more medications for 3 months (January‐March 2017) were included. Sociodemographic, pharmacological, potential drug interactions, and prescribers' variables were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…But patients already taking minimum five medications in 2014 were not excluded from the analysis. Furthermore, a recent study on factors related to the intake of minimum 15 medications found that a large majority of prescriptions was provided by the GP 34 . While this might only concern a reflection of the current primary healthcare organisation, it also supports our findings regarding GP contacts being associated with polypharmacy, bearing in mind the potential bidirectional nature of this association.…”
Section: Discussionsupporting
confidence: 88%
“…But patients already taking minimum five medications in 2014 were not excluded from the analysis. Furthermore, a recent study on factors related to the intake of minimum 15 medications found that a large majority of prescriptions was provided by the GP 34 . While this might only concern a reflection of the current primary healthcare organisation, it also supports our findings regarding GP contacts being associated with polypharmacy, bearing in mind the potential bidirectional nature of this association.…”
Section: Discussionsupporting
confidence: 88%
“…In studies conducted by this research group, we found a prevalence of excessive polypharmacy of approximately 108.4 per 100 000 people. It was also found that many patients were receiving 20 or more medications monthly (average 20.1 ± 4.5 drugs per patient), which lead us to propose that there is a new category of polypharmacy that we have decided to call “extreme polypharmacy.” This category deserves special attention because there are many consequences that can be derived from polypharmacy; it has been observed that polypharmacy raises the risk of adverse reactions (up to 82% for those patients who receive seven or more medications vs 13% in those who receive only two), the potential for interactions, a lack of adherence to treatment and decreased functional status in elderly patients …”
mentioning
confidence: 99%
“…In all cases, extreme polypharmacy is aggravated by therapeutic duplications (more than one antiulcer, antidepressant, or hypnotic medication, among others) from the care provided by multiple physicians in different specialties who do not adjust their medications according to those already prescribed by others. This leads to a greater number of possible drug‐drug interactions and an increased risk of adverse events, which may go unnoticed by all of the prescribers . In addition, the costs of care become very expensive (average: U.S. $272.5 per month, range U.S. $34.9‐3840.2 per month), which impacts health systems and deserves special care from physicians and decision makers.…”
mentioning
confidence: 99%
“…A pharmacy dispensing company (Audifarma SA) was identified in the SLR as the most commonly used database for RWE 34,42,61,63,72,73,94‐98,100‐109,111‐115,117,118,120,122‐131,134‐141,163,168,242,301,310 . It contains demographic data, diagnosis by ICD‐10, and drug dispensation records coded by the Anatomical Therapeutic Chemical (ATC) classification, which can be used to identify comorbidities, drug‐to‐drug interactions, medication errors, adverse events, and calculate adherence rates.…”
Section: Resultsmentioning
confidence: 99%